1989
DOI: 10.1051/lait:198911
|View full text |Cite
|
Sign up to set email alerts
|

Revue bibliographique : la fraction protéose-peptones du lait

Abstract: (reçu le 12-11-1987, accepté le 3-6-1988) Résumé -Les constituants de la fraction protéose-peptones du lait de vache sont décrits. Ils sont divisés en 2 classes en fonction de leur origine : d'une part les hydrolysats qui comprennent les composants 5 et 8 ainsi que de nombreux polypeptides résultant de l'hydrolyse des caséines par les protéases natives du lait; d'autre part des protéines, dont le composant 3, ainsi que des protéines majeures résiduelles. La composition et la concentration des protéose-pepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In addition, as described in "Materials and methods", CGMP was isolated from a whey protein concentrate by protein precipitation with trichloroacetic acid (TCA). It has previously been demonstrated that by stuch a precipitation with TCA, the components of the proteosepeptone fraction remaining with whey proteins are quantitatively precipitated (Paquet, 1989); consequently, contamination of our CGMP preparation by the CPP P(1-28) was a priori very unlikely. To remove any lingering doubts, we subjected CPP, CGMP, and mixtures of the two caseinopeptide fractions to FPLC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as described in "Materials and methods", CGMP was isolated from a whey protein concentrate by protein precipitation with trichloroacetic acid (TCA). It has previously been demonstrated that by stuch a precipitation with TCA, the components of the proteosepeptone fraction remaining with whey proteins are quantitatively precipitated (Paquet, 1989); consequently, contamination of our CGMP preparation by the CPP P(1-28) was a priori very unlikely. To remove any lingering doubts, we subjected CPP, CGMP, and mixtures of the two caseinopeptide fractions to FPLC.…”
Section: Discussionmentioning
confidence: 99%
“…The second group of proteins comprises the hydrophobic fractions of glycoproteins whose main component is called PP3 49 . The first group, the non-hydrophobic fraction, consists of peptides resulting from natural proteolysis of caseins and identified as components PP5, PP8-fast and PP8-slow, highly soluble.…”
Section: Figurementioning
confidence: 99%
“…PP fraction was separated from raw bulk milk according to the procedure described by Paquet (1989). The purified fraction was washed twice with water and freeze dried.…”
Section: Preparation Of Proteose Peptonesmentioning
confidence: 99%